Disinfectant natural rubber films filled with modified zinc oxide nanoparticles: Synergetic effect of mechanical and antibacterial properties - A. Krainoi; K. Poomputsa; E. Kalkornsurapranee; J. Johns; L. Songtipya; R. L. Nip; Y. Nakaramontri (eXPRESS Polymer Letters)
Disinfectant natural rubber (NR) film filled with nano-zinc oxide (ZnOnp) was prepared via latex processes. In addition, modification of ZnOnp was done by coating calcium carbonate (CaCO3) at the ratios of 90:10 and 60:40 (ZnOnp-Ca10 and ZnOnp-Ca40). Mechanical and thermo-mechanical properties, together with the unique anti-microbial activity of the resulting NR film products, were studied in detail. It was found that the nature of ZnO dispersion plays an important role in the improvement of the properties of NR films. Enhancement in the properties of NR was noticed for the films by the addition of ZnOnp-Ca10 and a reduction in properties was observed in the case of unmodified ZnOnp. Van-der Waals force of attraction among the ZnOnp particles and the improved degree of crosslinking of NR molecules are the reasons for the property enhancement. The results are well correlated with qualitative and quantitative determinations against gram-negative E. coli anti-microbial studies. Usage of modified-ZnOnp effectively kills bacteria through the formation of ROS and Zn++, which transfer across the NR molecules via electrostatic forces. Hence, it can be effectively used in the dipping process to develop gloves, condoms, clothes etc.